2021
DOI: 10.3390/ijerph182211822
|View full text |Cite
|
Sign up to set email alerts
|

Students with Autism Spectrum Disorders and Their First-Year College Experiences

Abstract: Using data from the 2019 CIRP Freshman Survey and the Your First College Year (YFCY) from the Higher Education Research Institute at UCLA, this study explores the differences between the characteristics and behaviors of the first-year students with autism spectrum disorders (17) and those of students with learning disabilities (102). The findings indicate that the characteristics of these two groups of first-year college students were similar except for gender, ethnicity, first college generation, and parents’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 44 publications
0
19
0
2
Order By: Relevance
“…Van Hees et al (2015), Thompson et al (2019), Cox et al (2021), Pectu et al (2021) found that neurodivergent students faced many challenges in their day-to-day experiences within a HEI. This study similarly found that disabled students faced many challenges within the environment, but the challenges were perceived as acting as barriers to engagement and as obstacles that needed to be overcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Van Hees et al (2015), Thompson et al (2019), Cox et al (2021), Pectu et al (2021) found that neurodivergent students faced many challenges in their day-to-day experiences within a HEI. This study similarly found that disabled students faced many challenges within the environment, but the challenges were perceived as acting as barriers to engagement and as obstacles that needed to be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…In line with other studies (Cox et al, 2021;Krieger et al, 2018;Thompson et al, 2019;Van Hees 2015) this study found that students faced many challenges within the environment that were not conducive to studying, learning or connecting socially with the college community. Van Hees et al (2015), Thompson et al (2019), Cox et al (2021), Pectu et al (2021) found that neurodivergent students faced many challenges in their day-to-day experiences within a HEI. This study similarly found that disabled students faced many challenges within the environment, but the challenges were perceived as acting as barriers to engagement and as obstacles that needed to be overcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first UDL principle is Provide multiple means of engagement 8. Affective networks located in the interior or central regions of the brain help process and regulate information 9.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This lack of recognition may disadvantage autistic students academically (Clouder et al, 2020). In addition, autistic college students report that on-campus activities are not accessible (Davidson et al, 2021) and have low utilization of campus mental health and disability services, suggesting the need to increase campus accessibility (Petcu et al, 2021).…”
Section: The Role Of Autism and Neurodiversity Acceptance In Higher E...mentioning
confidence: 99%